Perlindungan Hukum bagi Pihak yang Tidak Tercantum Namanya dalam Sertipikat (Beneficiary) dalam Perjanjian Kepemilikan Bersama Hak Atas Tanah - Cholif Chomsyah Rozaly (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
Among the models of "joint ownership agreements" are agreements between persons holding common land rights that agree that only one person is named in the certificate (called a nominee) while the other is not included in the certificate (called a beneficiary). This paper answers questions ranging from (1) legal protection to beneficiaries of bad faith nominee, and (2) legal settlement in the event of a dispute between nominee and beneficiary. The conclusions of this paper are (1) the protection of the law for the beneficiary of the harm done by the nominee can be done through the means of repressive law protection, namely dispute settlement in court, and (2) the legal settlement of the dispute between the nominee and the beneficiary may be settled through litigation and non-litigation, (in the form of: negotiation, mediation, conciliation and arbitration).